Comparing hemostatic and adhesion prevention effects of different types of nasal packings used post-septoplasty viz medicated gauze packing, glove finger packing and merocel packing (Bangladesh Journal of Otorhinolaryngology, 2012)
Aim: To compare the adhesion prevention and hemostatic effects of different types of nasal packing viz. medicated gauze packing, glove finger packing and merocel packing. Study Design: Prospective Study, in which 105 patients were, enrolled with effect from September 2011 to March 2012.Methods: This study was done in postgraduate department of ENT - HNS in Govt. Medical College, Srinagar. 105 patients undergoing septoplasty were randomly distributed in three groups, Group A, Group B, and Group C. Group A patients were packed postoperatively with medicated gauze packing, Group B with glove finger packing and Group C with merocel packing. Patients were then examined and regularly observed and followed for post-septoplasty hemorrhage and adhesions.Results: The average number of cotton balls used to clean the blood soakage on day one was 10 in Group A, 13 in Group B and 15 in Group C. On comparing the results of medicated gauze packing with merocel packings, the difference was not statistically significant(p